2022
DOI: 10.1002/cam4.4835
|View full text |Cite
|
Sign up to set email alerts
|

DDX24 promotes metastasis by regulating RPL5 in non‐small cell lung cancer

Abstract: Purpose: Non-small cell lung cancer (NSCLC) is a leading cause of cancer death, and metastasis is a crucial determinant of increased cancer mortality. DDX24 has garnered increased attention due to its correlation with tumorigenesis and malignant progression. However, the correlation between DDX24 and NSCLC remains unclear.Methods: DDX24 expression in NSCLC tissues and survival rate of patients was analyzed using bioinformatic analysis. Transwell assays, wound-healing assays, and tail vein lung colonization mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…NPC2 is a tumor suppressor by modulating MAPK/ERK signaling in primary hepatocellular carcinoma 40 . DDX24 has been demonstrated to be highly expressed in non-small cell lung cancer and associated with unfavourable clinical outcomes, with the silencing of DDX24 remarkably restraining cell migration and invasion in vitro and in vivo 41 . In this study, we include these genes to generate a prognostic risk signature for forecasting the clinical outcome of GC patients and found that the predictive capability of the risk signature is prior to each single gene.…”
Section: Discussionmentioning
confidence: 99%
“…NPC2 is a tumor suppressor by modulating MAPK/ERK signaling in primary hepatocellular carcinoma 40 . DDX24 has been demonstrated to be highly expressed in non-small cell lung cancer and associated with unfavourable clinical outcomes, with the silencing of DDX24 remarkably restraining cell migration and invasion in vitro and in vivo 41 . In this study, we include these genes to generate a prognostic risk signature for forecasting the clinical outcome of GC patients and found that the predictive capability of the risk signature is prior to each single gene.…”
Section: Discussionmentioning
confidence: 99%
“…HA‐p65, Flag‐Ub, and Myc‐RNF182 were transfected into 293T cells. After 48 h, the cells were treated with 20 μM MG132 (M7449; Sigma‐Aldrich) for 12 h 16 and then harvested for Co‐IP following the instruction manual of the kit (AM001‐01; ACE Biotechnology). In brief, the cells were lysed and centrifuged at 13,000 g for 10 min to discard the cell debris.…”
Section: Methodsmentioning
confidence: 99%